Development of multifunctional sandwich panels for integrated rehabilitation of RC-buildings: characterization of the components - Sousa, Christoph de (2018)
This research work deals with the development of a sustainable multifunctional composite sandwich panel for reinforced concrete (RC) frame buildings built in Portugal until the mid-1980s, which require structural and thermal-comfort rehabilitation. The sandwich panel, aimed specifically for interventions on building envelopes (refurbishment of building facades), is characterized by three main components: (i) thin outer concrete layers reinforced with recycled steel fibres (from post-consumed tyres), which fulfils the strength, ductility and durability requirements of the panel; (ii) a lightweight core layer made of polystyrene, which accomplishes thermal insulation requisites; and (iii) internal glass fibre reinforced polymer (GFRP) connectors that join the different layers of the panel, providing an adequate structural behaviour of the composite solution. The present paper focuses on the assessment of the relevant mechanical properties of the different components of the rehabilitation solution that is being developed, namely: (i) the Recycled Steel Fibre Reinforced Micro-Concrete (RSFRMC) developed specifically for this application; (ii) the GFRP connector; and (iii) the core material. After characterization of each individual component, additional tests are conducted on small specimens that are representative of the sandwich panel solution under development in order to assess the overall composite performance in shear and compression loading. The experimental work is described, and the most relevant results are presented and discussed.